Comparison of economic loss between generic drug and patent drug in stock-out and stagnant condition at Surabaya Islamic Hospital, Indonesia - Thinni Nurul Rochmah; Dwi Ratnasari; Hanin Dhany Robby (AOSIS, 2019)
The condition of stagnant and stock-out might cause economic loss and indicate ineffective and inefficient drug inventory management in the hospital. This study aims to compare the economic loss between generic drug and patent drug in stagnant and stock-out condition at Surabaya Islamic Hospital. The research was observational descriptive with cross-sectional design. The study was conducted with sample of 148 generic drugs and 299 patent drugs at pharmacy unit, Surabaya Islamic Hospital. The data was analyzed using independent t-test. The result showed different stagnant and stock put (p-value) experience in drug inventory between generic drug (70%) and patent drug (30%). The t-test in economic loss showed no difference between generic drug and patent drug stagnant (p-value=0.75) and stock-out (p-value=0.86) experience. The economic loss of generic drug experienced stagnant and stock-out in July-December 2015 with the amount up to IDR 86,476,696, while patent drug experienced loss both stagnant and stock-out up to IDR 88,349,589 in October 2016-March 2017. The study concluded that both conditions were disadvantageous for hospital's revenue and inventory management.